Risk Compensation after COVID-19 Vaccination - Jisoo Hwang; Seung-sik Hwang; Hyuncheol Bryant Kim; Jungmin Lee; Junseok Lee (Institute of Labor Economics (IZA), 2023)
This paper studies the causal impacts of vaccine eligibility on social distancing behaviors (risk compensation). We apply a regression discontinuity design around the birth date cutoff of vaccine eligibility using large, high-frequency data from credit card and airline companies as well as survey data. We find no evidence of risk compensation although vaccine take-up increases substantially with eligibility. We find some evidence of self-selection into vaccine take-up based on perception towards vaccine effectiveness and side effects, but we do not find that the treatment effects differ between compliers and never-takers.
Keywords: I12; I18; 330; COVID-19; vaccine take-up; selection; risk compensation; social distancing